Mathematics education undergraduates’ personal definitions of the notion of angle of contiguity in Kinematics - Zakaria Ndemo; David Mtetwa (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2021)
The concept of a mathematical definition causes severe difficulties among students during problem solving and proving activities. Students’ difficulties with the use of mathematical definitions often arise from the fact that students are often given those definitions instead of constructing them. With the aim of developing an understanding of the kinds of student teachers evoked concept images of the notion of  angle of contiguity, a qualitative case study was conducted at one state university in Zimbabwe. Purposive sampling was used to select 28 mathematics undergraduate student teachers who responded to a test item. Qualitative data analysis was guided by ideas drawn from the theoretical framework of Abstraction in Context and idea of imperative features of a mathematical definition.  Student teachers written responses revealed that student teachers personal concept definitions consisted of ambiguous and irrelevant formulations that did not capture the essence of the idea of the angle of contiguity. In some cases their responses were not consistent with the definition of the angle of contiguity.  Although there were a few instances of adequate descriptions of the concept, (8 out of  32) these and the inadequate descriptors elicited can contribute significantly towards efforts intended to improve mathematics instruction.  Improved mathematics instruction will lead to enhanced conceptualizations of mathematics concepts.